دراسة تصنيفية للديدان وحيدات العائلMonogenea المتطفلة على أسماك الكارب العادي Cyprinus carpio والسلور Clarius Lazera في بحيرة سد صلاح الدين - سلمان حسن; غالية محمد; سفر غيث (Latakia University Journal -Biological Sciences Series, 2019)
This study included 127 of common carp and catfish, the sampling was done monthly and randomly from Lake of Salah-ALdeen Dam (ALsafraqia) during the period from July 2014 to June 2015. Four parasitic species of genus Dactylogyrus were isolated and classified on Common carp: D. arquatus, D. minutus , D. extensus and D. vastator, and three parasitic species of genus Gyrodactylus: G. medius, G. elegans on Common carp and G. rysavyi on Catfish Species of genus Dactylogyrus were isolated as mainly from the gills on Common carp only, while species of genus Gyrodactylus from skin and fins. The species D. vastator, G. rysavyi and G. elegans were recorded for the first time at the fresh Syrian Coast water. شملت هذه الدراسة 127 سمكة من الكارب العادي والسلور، حيث جرى الإعتيان شهرياً وبشكل عشوائي من بحيرة سد صلاح الدين (السفرقية) خلال الفترة الممتدة من تموز 2014 وحتى حزيران 2015. عُزلت وصُنّفت أربعة أنواع طفيلية تتبع للجنس Dactylogyrus على أسماك الكارب العادي وهي: D. arquatus, D. minutus , D. extensus, D. vastator، وثلاثة أنواع تتبع للجنس Gyrodactylus وهي: G. medius, G. elegans على أسماك الكارب العادي، و G. rysavyiعلى أسماك السلور. عُزلت أنواع الجنس Dactylogyrus بشكل رئيسي عن غلاصم أسماك الكارب العادي فقط، بينما أنواع الجنس Gyrodactylus أُخذت عن الجلد والزعانف. سجُّلت الأنواع D. vastator G. rysavyi, G. elegans, لأول مرة في المياه العذبة للساحل السوري.